Analisis Kinerja Dinas Koperasi, Usaha Mikro, Kecil, dan Menengah Kota Pekanbaru (Studi Kasus Pelaksanaan Tugas Pokok dan Fungsi dalam Pembinaan Koperasi di Pekanbaru - Hidayat, Roli; Yuliani, Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Abstract: The Analysis Performance Department of Cooperatives, Micro,Small, and Medium Pekanbaru City (Case Study Implementation Duty andFunction in Development Cooperative in Pekanbaru). This study aims to analyzethe performance of the Department of Cooperatives Pekanbaru SMEs in theimplementation of the main tasks and functions of cooperative development. Theresearcher used quality research with data analys descriptively. In collecting thedata, the researcher user interview thecnique, observation, dan documentation.These results indicate that the performance of the Department of CooperativesSMEs in the implementation of Pekanbaru duties and functions of cooperativedevelopment is still less than optimal. Then there are factors that affectperformance are factors encountered in the field of human resources developmentand the factors that affect the performance of cooperatives CooperativesPekanbaru SMEs in the implementation of the tasks and functions of cooperativedevelopment.Keywords: Performance, Objectives, Standards, Feedback, equipment or meansof Competence, Motive, Opportunity